Patterns and Drivers of Vertical Distribution of the Ciliate Community from the Surface to the Abyssopelagic Zone in the Western Pacific Ocean - Zhao, Feng; Filker, Sabine; Xu, Kuidong; Huang, Pingping; Zheng, Shan (Frontiers in Microbiology, 2017)
The deep sea is one of the largest but least understood ecosystems on earth. Knowledge about the diversity and distribution patterns as well as drivers of microbial eukaryote (including ciliates) along the water column, particularly below the photic zone, is scarce. In this study, we investigated the diversity of pelagic ciliates, the main group of marine microeukaryotes, their vertical distribution from the surface to the abyssopelagic zone, as well as their horizontal distribution over a distance of 1,300 km in the Western Pacific Ocean, using high-throughput DNA and cDNA (complementary DNA) sequencing. No distance-decay relationship could be detected along the horizontal scale; instead, a distinct vertical distribution within the ciliate communities was revealed. The alpha diversity of the ciliate communities in the deep chlorophyll maximum (DCM) and the 200 m layer turned out to be significantly higher compared with the other water layers. The ciliate communities in the 200 m water layer appeared to be more similar to those in deeper layers from 1,000 m to about 5,000 m than to the surface and DCM ciliate communities. Dominant species in the bathypelagic and abyssopelagic zone, particularly some parasites, were also detected in the 200 m layer, but were almost absent in the surface layer. The 200 m layer, therefore, seems to be an important “species bank” for deep ocean layers. Statistical analyses further revealed significant effects of temperature and chlorophyll a on the partitioning of ciliate diversity, indicating that environmental factors are a stronger force in shaping marine pelagic ciliate communities than the geographic distance.